SOPEZ: study for the optimization of ergonomics in the dental practice - musculoskeletal disorders in dentists and dental assistants: a study protocol - Daniela Ohlendorf; Laura Maltry; Jasmin Hänel; Werner Betz; Christina Erbe; Christian Maurer-Grubinger; Fabian Holzgreve; Eileen M. Wanke; Dörthe Brüggmann; Albert Nienhaus; David A. Groneberg (Journal of Occupational Medicine and Toxicology, 2020)
Abstract Background Musculoskeletal disorders (MSD) are common among dental professionals. The most common areas affected are the trunk, neck, shoulders and wrists. Current evidence suggests that the causes of MSD can be found in the physical demands of the profession. Posture and movement during treatment is influenced by the arrangement of the treatment concept (patient chair, equipment and cabinets). It has not been investigated whether the ergonomic risk differs between the treatment concepts. Methods To evaluate the prevalence of MSD in dental professionals, 1000 responses will be collected from a nationwide (Germany) online questionnaire (mod. Nordic Questionnaire and mod. Meyer questionnaire). In order to assess the ergonomic risk of the treatment techniques used in the four treatment concepts, 3D movement analyses are carried out with inertial sensors. For this purpose, 20 teams of dentists and dental assistants from four dental fields of specializations (generalists, orthodontists, endodontists and oral surgeons) and a student control group will be recruited. Each team will execute field specific standardized treatments at a dummy head. Measurements are carried out in each of the four treatment concepts. The data will be analyzed using the Rapid Upper Limb Assessment (RULA) which will be modified for the evaluation of objective data. Conclusions On the basis of these investigations, a substantial gain of knowledge regarding work-related MSD in the field of dentistry and its potential biomechanical causes is possible. For the first time, objective and differentiated comparisons between the four treatment concepts are possible for different fields of dental specialization. Up to now, statically held positions of the trunk and proximal upper extremities, but also the repetitive movements of the hands have been considered a risk for MSD. Since both are included in the RULA, dental activities can be assessed in a detailed but also global manner with regard to ergonomic risks.